Sensitivity of hepatitis C virus core antigen and antibody combination assays in a global panel of window period samples. Issue 10 (27th May 2015) - Laperche, Syria; Nübling, C. Micha; Stramer, Susan L.; Brojer, Ewa; Grabarczyk, Piotr; Yoshizawa, Hiroshi; Kalibatas, Vytenis; El Elkyabi, Magdy; Moftah, Faten; Girault, Annie; van Drimmelen, Harry; Busch, Michael P.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Hepatitis C virus (HCV) antigen and antibody combination assays have been launched as a cost‐effective alternative to nucleic acid testing (NAT) for reducing the antibody‐negative window period (WP). Later, a HCV antigen chemiluminescence immunoassay (CLIA) became available. STUDY DESIGN AND METHODS A panel composed of 337 HCV NAT–yield samples that were characterized for viral load (VL) and genotype was used to compare the sensitivity of two combination enzyme‐linked immunosorbent assays (Monolisa, Bio‐Rad; and Murex, formerly Abbott) and a HCV antigen CLIA (Abbott). Analytic sensitivity was compared with HCV RNA detection using Ultrio (Grifols) by testing serial dilutions of 10 genotype (gt)1 to gt4 samples. RESULTS HCV antigen CLIA detected 92.4% of samples, whereas Monolisa and Murex detected 38.3 and 47.5%, respectively. In the HCV RNA VL range of 105 to 107 IU/mL, Monolisa and Murex detected 38% to 56% of gt1, 85% to 78% of gt2, and 21% to 37% of gt3. The overall geometric mean 50% limit of detection (range) of Ultrio on gt1 to gt4 dilution series was 3.5 (1.2‐7.7) copies/mL, compared to 3.3 × 106 (4.4 × 105‐2.7 × 107), 3.4 × 106 (2.2 × 105‐4.2 × 107), and 2728 (415‐7243) copies/mL for Monolisa, Murex, and HCV antigen CLIA, respectively. CONCLUSION Analytical sensitivity of NAT was on average 1 million‐ and 780‐fold higher than combination assays and HCV antigen CLIA, respectively. Relative sensitivities of combination assays differed for genotypes with Murex being more sensitive for gt1 and gt3 and Monolisa more sensitive for gt2. Although being less sensitive than NAT, combination assays could be considered in resource‐limited settings since they detect 38% to 47% of seronegative WP donations.